2021
DOI: 10.1007/s12144-021-02305-2
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between self-esteem and self-compassion in socially anxious

Abstract: Fear of evaluation and a negative view of the self are the core aspects of social anxiety. Self-compassion and self-esteem are two distinct positive attitudes toward the self, which are positively related to each other, well-being and good psychological functioning. It is less clear, however, how they interplay in socially anxious individuals and if self-compassion may reduce the negative effect of low self-esteem on social anxiety. The current research aimed at evaluating the directional links between those c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 40 publications
0
12
0
6
Order By: Relevance
“…Based on this theory, this study further verified and enriched this theory by using the positive prediction of appearance anxiety on social anxiety and the negative prediction of self-compassion. Notably, in contrast to self-esteem, self-compassion has no negative costs or consequences and is associated with positive mental health outcomes ( 40 ). Appearance anxiety can lead to a negative evaluation of oneself, resulting in a continuous decrease in self-compassion levels and a state of social anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this theory, this study further verified and enriched this theory by using the positive prediction of appearance anxiety on social anxiety and the negative prediction of self-compassion. Notably, in contrast to self-esteem, self-compassion has no negative costs or consequences and is associated with positive mental health outcomes ( 40 ). Appearance anxiety can lead to a negative evaluation of oneself, resulting in a continuous decrease in self-compassion levels and a state of social anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that there is a temporal link between self-esteem and self-compassion, in which the former serves as the foundation of the latter. Interesting, a number of studies have already explored this by testing mediation models in which self-compassion acts as the connecting variable between self-esteem (independent variable) and indices of psychological problems 87 , 88 and well-being 89 (dependent variable). Note also that the model includes potential downsides of both self-related concepts: defensiveness (including narcissistic tendencies) in the case of self-esteem and passivity (in the form of self-indulgence and self-pity) in the case of self-compassion, which may undermine the effectivity of the self-related screen against the drawbacks in life.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our present findings provide increasing evidence that self-compassion may be a protective factor (Neff, 2003 ). For example, Holas et al ( 2021 ) demonstrated that self-compassion significantly predicts empathy in almost all areas of psychology, including positive psychology, psychological health, motivation, and interpersonal functioning, in which self-compassion plays a role in increasing empathy via self-esteem.…”
Section: Discussionmentioning
confidence: 99%